Multifunctional aloe vera-based biomaterial for vital pulp therapy: an in vivo evaluation - Namazi, Sharon S.; Oliveira, Pedro Henrique Chaves de [UNESP]; McDonald, Neville J.; Cavalcanti, Bruno; Sasaki, Hajime; Bottino, Marco C.; Dal-Fabbro, Renan (Springer Nature, 2025)
This study aimed to evaluate the effects of Gelatin methacryloyl/Aloe vera (GelMA/AV) scaffolds, both alone and in combination with mineral trioxide aggregate (MTA), on pulp inflammatory response and mineralized tissue formation in a rat model of pulp exposure. GelMA/AV nanofibers (70:30) were fabricated via electrospinning and photocrosslinked. Twenty-four rats were randomly assigned to three groups (n = 8/ group): GelMA/AV, GelMA/AV + MTA, and MTA (control). Following pulp exposure of the first upper molars (n = 2/animal), the materials were placed over the exposed pulp as the pulp capping agent, and MTA was applied or not, depending on the group. The cavities were then sealed with glass ionomer. Animals were euthanized at 7 or 28 days post-procedure for histological, immunohistochemical, and micro-computed tomography (micro-CT) analyses. Data were analyzed using one-way or two-way ANOVA at a 5% significance level. Micro-CT analysis at 28 days revealed new hard tissue formation in the pulp chamber across all groups. GelMA/AV + MTA demonstrated comparable mineralized volume and tissue mineral density to MTA. Histologically, the GelMA/AV + MTA group exhibited a significantly lower cell count than the MTA and GelMA/AV groups at 28 days. However, for macrophage polarization, the GelMA/AV + MTA exhibited a similar expression of CD163-positive (M2) and iNOS-positive (M1) cells compared to the MTA. Lastly, GelMA/AV + MTA also showed expression of nestin and DMP1 at 28 days, indicating active mineralization. In conclusion, a thin GelMA/AV sublayer beneath MTA preserves MTA-driven mineralization but does not reduce pulp inflammation or enhance mineralization beyond MTA in this model. Optimization of AV dosing/formulation and longer follow-up are necessary before clinical translation.